Molecular Mechanism Responsible for the Priming of Macrophage Activation - Deng, Hui (American Society for Biochemistry and Molecular Biology, 2013)
Host macrophages can be preprogrammed into opposing primed or tolerant states depending upon the nature and quantities of external stimulants. The paradigm of priming and tolerance has significant implications in the pathogenesis and resolution of both acute and chronic inflammatory diseases. However, the responsible mechanisms are not well understood. Here, we report that super low dose bacterial endotoxin lipopolysaccharide (LPS), as low as 5 pg/ml, primes the expression of proinflammatory mediators in macrophages upon a second high dose LPS challenge (100 ng/ml), although 5 pg/ml LPS itself does not trigger noticeable macrophage activation. Mice primed with super low dose LPS (0.5 μg/kg body weight) in vivo experience significantly elevated mortality following a second hit of high dose LPS as compared with saline-primed control mice. Mechanistically, we demonstrate that LPS primes macrophages by removing transcriptional suppressive RelB through interleukin receptor-associated kinase 1 and Tollip (Toll-interacting protein)-dependent mechanisms. This is in sharp contrast to the well documented RelB stabilization and induction by high dose LPS, potentially through the phosphoinositide 3-kinase (PI3K) pathway. Super low dose and high dose LPS cause opposing modulation of interleukin receptor-associated kinase 1 and PI3K pathways and lead to opposing regulation of RelB. The pathway switching induced by super low versus high dose LPS underscores the importance of competing intracellular circuitry during the establishment of macrophage priming and tolerance.